Distribusi Beras Murah Untuk Masyarakat Oleh PT. Jatim Grha Utama Dalam Gelaran Operasi Pasar Lumbung Pangan - Maulana Yogi Aditya Dwi Putra; Rosyidatuzzahro Anisykurilillah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study examines the implementation of cheap rice distribution by PT. Jatim Grha Utama through the Food Barn Market Operation and its impact on people's food accessibility. Qualitative research methods are used by collecting data through observation, interviews, and documentation. The results of the research show that PT. Jatim Grha Utama succeeded in carrying out the distribution of cheap rice effectively. A well-organized distribution strategy allows the company to reach the public with cheap rice through scattered distribution points. This research provides an understanding of the implementation of cheap rice distribution in increasing people's food accessibility and suppressing regional inflation. Food Storage Market Operation Program by PT. Jatim Grha Utama makes a positive contribution in achieving better food security.